2015
DOI: 10.1097/nen.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Classic Ras Proteins Promote Proliferation and Survival via Distinct Phosphoproteome Alterations in Neurofibromin-Null Malignant Peripheral Nerve Sheath Tumor Cells

Abstract: Neurofibromin, the tumor suppressor encoded by the neurofibromatosis type 1 (NF1) gene, potentially suppresses the activation of H-Ras, N-Ras and K-Ras. However, it is not known whether these classic Ras proteins are hyperactivated in NF1-null nerve sheath tumors, how they contribute to tumorigenesis and what signaling pathways mediate their effects. Here we show that H-Ras, N-Ras and K-Ras are coexpressed with their activators, (guanine nucleotide exchange factors), in neurofibromin-null malignant peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…Cyclin D1, a cell cycle promoter, was downregulated by silencing CNN1 and CNN2, explaining that why cell cycle was arrested [27,28]. the K-ras and p53 signal pathways play important roles in colorectal cancer cell lines, as reported in many solid cancers [29][30][31][32][33][34]. We found that the p53 signal pathway was suppressed by upregulating CNN2 or silencing CNN1, which interacted with cyclin D1, arresting the cell cycle.…”
Section: Discussionsupporting
confidence: 51%
“…Cyclin D1, a cell cycle promoter, was downregulated by silencing CNN1 and CNN2, explaining that why cell cycle was arrested [27,28]. the K-ras and p53 signal pathways play important roles in colorectal cancer cell lines, as reported in many solid cancers [29][30][31][32][33][34]. We found that the p53 signal pathway was suppressed by upregulating CNN2 or silencing CNN1, which interacted with cyclin D1, arresting the cell cycle.…”
Section: Discussionsupporting
confidence: 51%
“…However, only classic Ras proteins promote the survival of MPNST cells, whereas R-Ras proteins drive their migration. 29 Within the classic Ras subfamily, though, there appears to be functional redundancy; ablation of one subfamily member results in increased expression and activation of another subfamily member with little, if any, effect on proliferation. Tipifarnib inhibits only H-Ras, because other post-translational modifications such as geranylgeranylation allow K-Ras and N-Ras to be Figure 1 In plexiform neurofibromas and MPNSTs, neurofibromin loss deregulates multiple proteins from both the classic Ras and R-Ras subfamilies.…”
Section: Oncogenomics In Mpnst Modelsmentioning
confidence: 99%
“…Although initial results indicate that this is the case, note that the full repertoire of Ras-dependent signaling pathways activated in NF1-null peripheral nerve sheath tumors has not yet been defined. Indeed, a recent study that examined changes occurring in the phosphoproteome after inhibition of classic Ras signaling 29 showed that classic Ras signaling controlled multiple additional signaling cascades in MPNSTs. It will be important to determine which of these signaling cascades contribute to tumorigenesis and whether they are further dysregulated by additional mutations arising during neurofibroma-MPNST progression.…”
Section: Oncogenomics In Mpnst Modelsmentioning
confidence: 99%
“…The RAS oncogene family is extraordinarily common in diverse cancers, and members of the family play important roles in tumorigenesis. 27 RAS promotes tumorigenesis by activating several intracellular signal transduction cascades, including the RAS/MAPK/ERK and PI3K/AKT pathways. 28 , 29 In gliomas, miR-143 inhibits N-RAS expression by these two pathways.…”
Section: Discussionmentioning
confidence: 99%